Atmospheric Pollution and Consumption Patterns in Spain: An Input-Output Approach - Mònica Serrano; Jordi Roca (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper analyses the relationship between Spanish household consumption patterns and atmospheric pollutant emissions in 2000. Applying an input-output approach we estimate the relative responsibility of different types of households in the emissions of nine different atmospheric pollutants: the six greenhouse gases (CO2, CH4, N2O, SF6, HFCs and PFCs) regulated by the Kyoto protocol and three other gases (SO2, NOx and NH3). We combine input-output tables, national consumer survey statistics and environmental pollution satellite accounts into an environmental extended input-output model. We also analyse the assumptions required in order to apply the model to available data. We find that there is a positive and very high relationship between the level of household expenditure and the direct and indirect emissions generated by household consumption. However, the emission intensities tend to decrease with the expenditure level for the different atmospheric pollutants, with the exception of the synthetic greenhouse gases (SF6, HFCs and PFCs).
Keywords: C67; D12; Q53; 330; Input-Output Analysis; Consumption Pattern; Atmospheric Pollution; Verbraucherausgaben; Luftverunreinigung; Input-Output; Spanien